Application Of Data Mining For Prediction Of Students Out Of College With The Method Algorithm C4.5 - suandi daulay; wira apriani; yuda perwira (Marqcha Institute, 2022)
This research was conducted to predict students dropping out of private universities, the student department needs to pay attention to students who have the potential to drop out so that they can be detected faster to make an approach with students so they don't drop out of college, with the help of data mining so that data -The data collected is useful information and with the C4.5 method so that predictions become accurate to detect students who have the potential to drop out of college. As for the results of this study, it is known that the most influential variable for students dropping out of college is marked by UKT Not Current Then Often Absent Then Gender Male whose graduation year is not recently graduated (not fresh graduate)